Novel reports of distal hereditary neuropathy due to mutations of SIGMAR 1 from India - Shah, Arjun G.; Chaudhary, Gaurav; Mahto, Anuradha P.; Maniyar, Aamna; Chheda, Akash; Jagiasi, Kamlesh A. (International Journal of Advances in Medicine, 2024)
Distal hereditary neuropathies (dHMN) are hereditary neuromuscular disorders characterized by predominant distal motor neuropathy, leading to muscle atrophy, with a striking preservation of the sensory nervous system. While there is occasional overlap with Charcot-Marie-tooth disease (CMT) and familial amyotrophic lateral sclerosis (fALS), these conditions typically represent distinct entities with better prognosis. Numerous gene defects are associated with dHMN, and on-going research continues to unveil novel mutations. Among these, the mutation in the sigma non-opioid intracellular receptor 1 gene (SIGMAR1) has been identified across diverse populations. SIGMAR1 encodes a non-opioid endoplasmic reticulum protein present in both the central and peripheral nervous systems, playing a crucial role in neuronal survival and maintenance. Notably, SIGMAR1 gene mutations are linked to two distinct motor neuron disease phenotypes: fALS and dHMN. This signifies the broad impact of SIGMAR1 mutations on the neurogenetic landscape, contributing to the understanding of the complex interplay between genetic factors and motor neuron disorders. The continuous discovery of new mutations emphasizes the dynamic nature of research in this field, shedding light on the intricate mechanisms underlying these debilitating conditions.